2015
DOI: 10.4236/jhrss.2015.34025
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Training and Development on Employee Performance and Effectiveness: A Case Study of District Five Administration Office, Bole Sub-City, Addis Ababa, Ethiopia

Abstract: The focus of this study was to determine the impact of training and development on the employees' performance and effectiveness at District Five Administration Office, Addis Ababa, Ethiopia. In this study we employed cross sectional institutional based quantitative research method. Data were collected using Likert's scale tool from 100 employees after selecting participants using systematic random sampling technique. Ninety-four complete questionnaires with a response rate of 94% were considered during analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
96
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(111 citation statements)
references
References 12 publications
13
96
0
2
Order By: Relevance
“…Therefore, if training and development increase, employee performance will increase. Previous researchers have also come out with similar findings (Tahir, Yousafzai, Jan, Hashim, 2014;Asfaw, Argaw, Bayissa, 2015). A very strong and positive influence of rewards and recognition on the performance of the employees is visible since beta coefficient is 1.124 with a p-value of 0.000 (< .05).…”
Section: Resultssupporting
confidence: 68%
“…Therefore, if training and development increase, employee performance will increase. Previous researchers have also come out with similar findings (Tahir, Yousafzai, Jan, Hashim, 2014;Asfaw, Argaw, Bayissa, 2015). A very strong and positive influence of rewards and recognition on the performance of the employees is visible since beta coefficient is 1.124 with a p-value of 0.000 (< .05).…”
Section: Resultssupporting
confidence: 68%
“…The level of HOTS training program is high in reaction, learning, knowledge and skills, organizational support, and perceptions of student learning. This study supports the findings by Asfaw, Argaw, and Bayissa (2015) on the impact of training and development on employee performance and effectiveness. Their study found that the training activities can help to increase the level of employees' potentials in performing their tasks and resulted in their effectiveness.…”
Section: Demographic Informationsupporting
confidence: 80%
“…Employee training involves providing the workforce with the required skills to suit them in accomplishing specific tasks (Asfaw, Argaw, & Bayissa, 2015). Employee training may be part of employee development initiative, which usually takes a long time and results in the enhancement of one's skills through unconscious and conscious learning processes (Asfaw et al, 2015).…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
“…Employee training may be part of employee development initiative, which usually takes a long time and results in the enhancement of one's skills through unconscious and conscious learning processes (Asfaw et al, 2015). Employee training is imperative in improving the competency of the workforce so 499 that the organization can be able to maximize the effectiveness and efficiency of its human capital (Shiryan, Shee, & Stewart, 2012).…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
See 1 more Smart Citation